2016
DOI: 10.1063/1.4940025
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of wind velocities in the upstream induction zone of a wind turbine using scanning continuous-wave lidars

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
79
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 14 publications
15
79
1
Order By: Relevance
“…Three-dimensional wind-field measurements made using dual-Doppler intersecting RHI scans and using continuity to estimate the vertical velocity were used to study flow upstream and downstream of a utility-scale wind turbine . Three-dimensional wind and turbulence measurements using fully coordinated short-range continuous wave triple lidars (Mikkelsen et al, 2008;Simley et al, 2016) and long-range triple lidar scanning Vasiljević et al, 2016) have been demonstrated to provide high quality measurements of complex flow. In addition, manually coordinated triple lidar measurements (Wang et al, 2016) were also tested and showed promise in measuring the 3-D wind fields operationally.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional wind-field measurements made using dual-Doppler intersecting RHI scans and using continuity to estimate the vertical velocity were used to study flow upstream and downstream of a utility-scale wind turbine . Three-dimensional wind and turbulence measurements using fully coordinated short-range continuous wave triple lidars (Mikkelsen et al, 2008;Simley et al, 2016) and long-range triple lidar scanning Vasiljević et al, 2016) have been demonstrated to provide high quality measurements of complex flow. In addition, manually coordinated triple lidar measurements (Wang et al, 2016) were also tested and showed promise in measuring the 3-D wind fields operationally.…”
Section: Introductionmentioning
confidence: 99%
“…Branlard et al (2016) emphasize that further investigations are necessary to conclude whether the effects of the stagnation on the turbulence are systematic or not (see also Branlard, 2017, which is an expanded version of Branlard's thesis). Simley et al (2016) measure the turbulent inflow towards a Vestas V27 wind turbine using three synchronized continuous wave, scanning Doppler lidars. They clearly see the stagnation in front of the rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Branlard et al (2016) emphasize that further investigations are necessary to conclude whether the effects of the stagnation on the turbulence 20 are systematic or not (see also Branlard, 2017, which is an expanded version of Branlard's thesis). Simley et al (2016) measure the turbulent inflow towards a Vestas V27 wind turbine using three synchronized continuous wave, scanning Doppler lidars. They clearly see the stagnation in front of the rotor and also a slight rotation of the inflow.…”
mentioning
confidence: 99%